Competitive Strategies in The Lodging Service Sector : Five Porter Analyses And Case Study SWOT Analysis - Awdita Citra Birru; Sudarmiatin Sudarmiatin; Agus Hermawan (Profesional Muda Cendekia Publishing, 2022)
Booking lodging services using online applications is a strategy used by companies in marketing their services. One of the lodging booking platforms is RedDoorz and OYO. Along with the emergence of this technology and information, causing every innkeeper to have a competitive strategy. This study aims to determine the product differentiation strategy, the competitive strategy with porter's five forces analysis, the company's condition using SWOT analysis, and customer satisfaction with the SERVQUAL dimension in lodging services Malang. The research subjects are lodging services in Malang that market their products using the RedDoorz and OYO platforms. The subjects of this research include Omega Guest House, Bunga Cengkeh Homestay, Aurila Homestay, and Kina Family Residence. Data were analyzed descriptively qualitatively with Porter's Five Forces analysis, SWOT analysis and SERVQUAL dimensions. The study results indicate that the lodging service sector in Malang is almost entirely only implementing a differentiation strategy based on price and service. The SWOT analysis results show the second quadrant point, strategy diversification, which means this position proves that a business is strong but faces big challenges during the Covid-19 pandemic. So you have to prepare a business strategy that has been prepared based on the results of the company's SWOT analysis. Business owners in the field of services such as lodging in Malang must give full attention to customers because when the level of satisfaction is high it will not rule out the possibility, the visitor will return at another time, this full attention is called service quality or SERVQUAL